VIRILISING OVARIAN TUMOUR: A TERTIARY CENTRE EXPERIENCE - Sutharsan, Shamila (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND To determine the clinical features, a spectrum of imaging characteristics and histopathologic findings of virilizing tumours of the ovary. CASE A 69-year-old female presented with a 1-year duration of increasing hair growth over both arms and androgenic and male pattern facial hirsutism which needed facial hair trimming once a week. She attained menarche and menopause at the age of 12 and 55 respectively. She was diagnosed with hypertension and Graves’ disease at 30 years of age. She was clinically obese with a BMI of 30 kg/m2 , blood pressure 149/84 mmHg, deepening of voice and hirsutism score of 16. There was no clitoromegaly, no proximal myopathy, no cutaneous bruising or abdominal striae. The total testosterone level was >52.05 nmol/L (NR: 0.1-1.6) with normal ACTH, cortisol and DHEA-S. An abdominal CT scan showed a left ovarian mass measuring 7.3 x 7.4 x 5.4 cm with solid components and signs of peritoneal carcinomatosis; however, no calcification within the mass was noted. She underwent primary debulking total abdominal hysterectomy with bilateral salpingo-oophorectomy (TAHBSO), omentectomy and pelvic node dissection. Histopathological examination demonstrated steroid cell tumour of the ovary. Post-operatively, testosterone levels reduced to normal and showed improvement of alopecia and hirsutism on follow-up 6 months later. CONCLUSION In post-menopausal women the appearance of signs of virilization and high testosterone levels should be investigated systematically for underlying malignancy and to determine if the high testosterone levels are of an adrenal or ovarian origin. Failure of recognition will lead to a poor prognosis. In this patient, hematological investigations ruled out an adrenal cause however radiological imaging identified an ovarian etiology.